Understanding Ethical Performance through Ethical Competence, Organizational Justice, and Ethical Climate - Mutia Nurani; Meiske Claudia; Hastin Umi Anisah (International Journal of Social Science and Religion (IJSSR), 2026)
Ethical performance has become increasingly important in legislative institutions where integrity and accountability are essential for maintaining public trust. This study examines the mediating role of ethical climate in the relationship between ethical competence, organizational justice, and ethical performance. Using a quantitative approach, data were collected from 120 members of five Regional Houses of Representatives (DPRD) in South Kalimantan, Indonesia, through proportionate stratified sampling. The proposed model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that ethical competence and organizational justice positively influence ethical performance and ethical climate. Ethical climate emerged as the strongest predictor of ethical performance, while organizational justice had the greatest effect on ethical climate. In addition, ethical climate significantly mediates the effects of ethical competence and organizational justice on ethical performance. These findings indicate that the interaction between individual ethical capability, perceptions of fairness, and organizational conditions shapes ethical behavior in legislative institutions. The study enriches the ethical performance literature by integrating individual and organizational factors within a single framework.